Analysis of inteins in the Candida parapsilosis complex for simple and accurate species identification - Prandini, Tâmara Heloísa Rocha [UNESP]; Theodoro, Raquel Cordeiro; Bruder-Nascimento, Ariane C. M. O. [UNESP]; Scheel, Christina M.; Bagagli, Eduardo [UNESP] (American Society for Microbiology, 2013)
Inteins are coding sequences that are transcribed and translated with flanking sequences and then are excised by an autocatalytic process. There are two types of inteins in fungi, mini-inteins and full-length inteins, both of which present a splicing domain containing well-conserved amino acid sequences. Full-length inteins also present a homing endonuclease domain that makes the intein a mobile genetic element. These parasitic genetic elements are located in highly conserved genes and may allow for the differentiation of closely related species of the Candida parapsilosis (psilosis) complex. The correct identification of the three psilosis complex species C. parapsilosis, Candida metapsilosis, and Candida orthopsilosis is very important in the clinical setting for improving antifungal therapy and patient care. In this work, we analyzed inteins that are present in the vacuolar ATPase gene VMA and in the threonyl-tRNA synthetase gene ThrRS in 85 strains of the Candida psilosis complex (46 C. parapsilosis, 17 C. metapsilosis, and 22 C. orthopsilosis). Here, we describe an accessible and accurate technique based on a single PCR that is able to differentiate the psilosis complex based on the VMA intein. Although the ThrRS intein does not distinguish the three species of the psilosis complex by PCR product size, it can differentiate them by sequencing and phylogenetic analysis. Furthermore, this intein is unusually present as both mini- and full-length forms in C. orthopsilosis. Additional population studies should be performed to address whether this represents a common intraspecific variability or the presence of subspecies within C. orthopsilosis. Copyright © 2013, American Society for Microbiology. All Rights Reserved.
Keywords: intein; threonine transfer RNA ligase; accuracy; Candida metapsilosis; Candida orthopsilosis; Candida parapsilosis; cladistics; controlled study; fungal gene; fungal strain; fungus identification; fungus isolation; gene function; gene identification; molecular phylogeny; nonhuman; polymerase chain reaction; priority journal; protein determination; protein function; sequence analysis; threonyl tRNA synthetase gene; vacuolar ATPase gene